Quantitative proton imaging from multiple physics processes: a proof of concept. (24th June 2015) - Bopp, C; Rescigno, R; Rousseau, M; Brasse, D
Abstract: Proton imaging is developed in order to improve the accuracy of charged particle therapy treatment planning. It makes it possible to directly map the relative stopping powers of the materials using the information on the energy loss of the protons. In order to reach a satisfactory spatial resolution in the reconstructed images, the position and direction of each particle is recorded upstream and downstream from the patient. As a consequence of individual proton detection, information on the transmission rate and scattering of the protons is available. Image reconstruction processes are proposed to make use of this information. A proton tomographic acquisition of an anthropomorphic head phantom was simulated. The transmission rate of the particles was used to reconstruct a map of the macroscopic cross section for nuclear interactions of the materials. A two-step iterative reconstruction process was implemented to reconstruct a map of the inverse scattering length of the materials using the scattering of the protons. Results indicate that, while the reconstruction processes should be optimized, it is possible to extract quantitative information from the transmission rate and scattering of the protons. This suggests that proton imaging could provide additional knowledge on the materials that may be of use to further improve treatment planning.